2009
DOI: 10.1103/physreva.79.064301
|View full text |Cite
|
Sign up to set email alerts
|

Distillability of entanglement in accelerated frames

Abstract: We study the entanglement distillability of bipartite mixed states of two modes of a free Dirac field as seen by two relatively accelerated parties. It is shown that there are states that will change from distillable into separable for a certain value of acceleration. We exemplify these criteria in the context of Werner states.Comment: 6 pages, 1 figur

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 9 publications
2
53
0
Order By: Relevance
“…This is exactly same as the density matrix obtained for the special case p = 1 [6,11]. Since the entanglement of ρ I,II has been studied elsewhere [6,11,53], it will not be presented here. The quantum discord, D(I : II), is evaluated and plotted in Fig.…”
Section: Bipartition Rob-antirobmentioning
confidence: 56%
“…This is exactly same as the density matrix obtained for the special case p = 1 [6,11]. Since the entanglement of ρ I,II has been studied elsewhere [6,11,53], it will not be presented here. The quantum discord, D(I : II), is evaluated and plotted in Fig.…”
Section: Bipartition Rob-antirobmentioning
confidence: 56%
“…Approaches to density matrices of Dirac bi-spinors often focus on deriving information content of such states when transformations to inertial and non-inertial frames are performed [33][34][35]. In such applications, the dynamics is described by a free Dirac Hamiltonian and are not straightforwardly generalized to include external fields.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the investigation of the quantum correlation in a relativistic framework is not only helpful to understand some key questions in the quantum information theory, but also plays an important role in the study of the entropy and information paradox [4,5] of the black hole. Following the pioneering work presented by Peres et al [6], many authors [7][8][9][10][11][12][13][14][15][16][17][18][19] considered the quantum entanglement in a relativistic setting. Recently, Adesso et al [20] discussed the entanglement sharing of a scalar field in the noninertial frame and found that the classical correlation is independent of the acceleration of the observer if the other observer stays stationary.…”
Section: Introductionmentioning
confidence: 99%